DESIGNING TASK-BASED SPEAKING MATERIALS USING AUTHENTIC TEXT: LEARNER AUTONOMY - Abd. Rahman (University of Muhammadiyah Purwokerto, 2016)
The roles of learners in language teaching are not only the receiver of the information but also the providers, collaborators, and decision-makers. In this case, the learners can provide and collaborate with the teacher to decide what materials and language competences the learners need to learn and achieve. Thus, the learning materials and tasks should represent the students’ needs that facilitate them to use the language in the real world. One of the materials that need to take into account is an authentic text. Authentic text as informa-tional input for interested participants, for building interpersonal relationship between the interested partici-pants, and for communicating meaning (Widodo: 2012). In line with this, the students can contribute an authentic text to be designed for interactive speaking task. The interactive speaking task I propose: compre-hending the text, making power point presentation from the text, explaining (playing a role as a speakers and participants in the seminar), responding to the explanation (questioning and answering). To design the ma-terial and the task using authentic text has to consider the eight principles as the basic theoretical framework for English for Specific Purposes (ESP) materials design. Keywords: Learner autonomy, task, authentic text, ESP